Non-canonical peptides bound to MHC - Day, S.; Ramsland, Paul; Apostolopoulos, V. (2009)
Central to the initiation of a T cell dependent immune response is the recognition of major histocompatibility complex (MHC) class I or class II molecules (in humans termed HLA and in mice termed H-2) bound to antigenic peptide. T cell receptors (TCR) have programmed specificity for particular peptide/MHC complexes, which ensures focused immune responses are generated against the antigen source. To design effective peptide based vaccines a comprehensive understanding of the specific interactions between MHC molecules and peptide, and of TCR recognition of MHC/peptide is valuable. We place particular emphasis on non-canonical bound peptides and their use in immunotherapy studies. © 2009 Bentham Science Publishers Ltd.